Effects of Gradual and Sudden Introduction of Perturbations on Adaptive Responses to Formant-Shift and Formant-Clamp Perturbations. - Sara-Ching Chao; Daliri, Ayoub (Journal of Speech, Language & Hearing Research, 2023)
tive responses to compensate for the errors. Unlike errors induced by formantshift perturbations, errors induced by formant-clamp perturbations do not correspond with the speaker’s speech (i.e., degraded motor-to-auditory correspondence). We previously showed that adaptive responses to formant-clamp perturbations are smaller than responses to formant-shift perturbations when perturbations are introduced gradually. This study examined responses to formant-clamp and formant-shift perturbations when perturbations are introduced suddenly. Method: One group of participants (n = 30) experienced gradually introduced formant-clamp and formant-shift perturbations, and another group (n = 30) experienced suddenly introduced formant-clamp and formant-shift perturbations. We designed the perturbations based on participant-specific vowel configurations such that a participant’s first and second formants of /ɛ/ were perturbed toward their /æ/. To estimate adaptive responses, we measured formant changes (0–100 ms of the vowel) in response to the formant perturbations. Results: We found that (a) the difference between responses to formant-clamp and formant-shift perturbations was smaller when the perturbations were introduced suddenly and (b) responses to suddenly introduced (but not gradually introduced) formant-shift perturbations positively correlated with responses to formant-clamp perturbations. Conclusions: These results showed that the speech motor system responds to errors induced by formant-shift and formant-clamp perturbations more differently when perturbations are introduced gradually than suddenly. Overall, the quality of errors (formant-shift vs. formant-clamp) and the manner of introducing errors (gradually vs. suddenly) modulate the speech motor system’s evaluations of and responses to errors.